The repercussions of the overlap within the roles of the Palestinian-Israeli negotiations on the outcomes of negotiating process: an analytical study - Mu'ala, Abdulsalam (m.r) Suleiman (2018)
This study explores the effects of the overlapping roles and objectives of the Palestinian-Israeli negotiations onto the outcomes of the negotiating process. The negotiation process is a functional center which plays a major role in resolving conflicts and simultaneously performs several other objectives. This has caused overlapping roles of the functional center between the major and the secondary ones. The interactional roles, which are the secondary one, are given priority over a functional center as the major role. This study therefore, examines the impact of the overlapping roles and objectives played by the functional center onto the negotiation process’s outcomes. The focus of this study is the Palestinian-Israeli negotiations from 1991 until 2001. This is a qualitative study, which employed interviews and document study as the main data collection methods. The respondents for the interviews were purposively sampled and the data gathered were descriptively and analytically examined. The role theory was adopted as the main framework for this study. The study investigates the following concerns, namely, whether or not the Palestinian-Israeli negotiation has the proper introduction. It also examines the extent to which the negotiation process followed theoretical rules and other bases of negotiation as well as analyses whether or not the negotiation process fulfilled the conditions, principles, and attributes of political negotiations. This study also explores the ability of the Palestinian negotiators to deal with other options of negotiation and the types of negotiation strategies adopted by the Israeli negotiators. It also examines several other aspects including the extent to which the agenda was negotiable, and whether or not the Palestinian negotiators were qualified to negotiate on such question, and the impact of the international political environment on the negotiating process. The major findings of this study shows that, the overlapping in negotiating roles have impacted negatively on the negotiation outcomes. The study also discovers that, among the major ones, the Palestinian-Israeli negotiation process did not meet the theoretical norms of political negotiations and the agenda negotiated was non-negotiable. The study suggests that, the Palestinian negotiators ought to reconsider the adoption of the negotiation options that they chose which so far, has not yielded any positive result